Effects of Sudden Drop in Salinity on Osmotic Pressure Regulation and Antioxidant Defense Mechanism of Scapharca subcrenata - Mo, Zhang; Li, Li; Ying, Liu; Xiaolong, Gao (Frontiers in Physiology, 2020)
Salinity is an important ecological factor that impacts the growth and survival of aquatic organisms. The salinity of seawater in coastal and estuarine areas is often subject to dynamic changes because of seasonal rainfall and continental runoff. Thus, the current study investigated the effects of sudden changes in salinity on the survival rate and osmotic pressure regulation mechanisms of bottom-sowing seedlings of the economically important ark shell, Scapharca subcrenata. By simulating the sudden changes that occur in seawater salinity after rainstorms, the results showed that the osmotic pressure of the hemolymph and Na+, K+, Ca2+, and Cl– concentrations first decreased and then increased. When the salinity decreased from 30‰ to 14‰, hemoglobin, soluble total protein, taurine, and total free amino acid gradually increased; maximum levels of hemoglobin, soluble total protein, and taurine occurred once the salinity increased to 22‰ at 96 h. After 96 h, the total free amino acid content increased until 144 h. The reactive oxygen species (ROS) content and total antioxidant capacity peaked at 96 h, whereas the expression of MnSOD and CAT increased earlier, indicating that, with continuous ROS generation, antioxidant defense mechanisms were activated to avoid oxidative damage. Expression of CTSC, CTSD, HSP20, and HSP70 was significantly higher than in the control group at 48 h (salinity level 14‰); the expression of HSP20, HSP90, MnSOD and GPx remained high, indicating that they were still required for osmotic pressure regulation to maintain the dynamic balance between the generation and removal of ROS as the salinity level increased. These results not only add to our basic understanding of the aquatic ecology of S. subcrenata, but also provide a theoretical ground for improving the survival rate of bottom-sowing, propagation, and release of S. subcrenata seedlings.